IMPLEMENTING RUNNING DICTATION GAME TO INCREASE SPEAKING SKILL OF THE STUDENTS - Muhimatul Murtafiah; Muawanah Muawanah (Aulada : Jurnal Pendidikan dan Perkembangan Anak, 2022)
Nowadays, there are many students in some school who felt bored, sleepy and languid during the learning process. Moreover, in the learning English process, most of students have though that learning English was hard. Because English has differences in spelling and the writing, students got difficulties and had less in speaking skill. Teacher found that most of them used their native language during the English lesson process. So that, the aims of the study is to know whether the communicative approach, exactly running dictation game effective for increasing the speaking skill of the students or not. The subject of this research will be the students at 11th grade of MA. Unggulan Amanatul Ummah Surabaya. This research will use observation and data recording to collect the data. Furthermore, the other aim is to know how to implement the running dictation in teaching English. This study will use observation and recording documentation to collect the data.